Enhancement effect of γ-irradiation pre-treatment on anaerobic digestion performance of kitchen wastewater. (1st January 2022) - Ling, Yongsheng; Wang, Hongxiao; Fei, Xionghui; Huang, Tian; Shan, Qing; Hei, Daqian; Chen, Ting; Zhang, Xiaojun; Jia, Wenbao
Abstract: In China, the annual output of kitchen wastewater with high oil content has exceeded 90 million tons, which poses a threat to the environment. Anaerobic digestion is considered a suitable treatment approach to realize the harmless and resource utilization of kitchen wastewater of the available bioresource. This study explored a pretreatment method based on gamma radiation to reduce the oil content in kitchen wastewater and improve its anaerobic digestion performance. In addition, response surface analysis was used to optimize the pretreatment conditions and build the production of kitchen wastewater gas prediction model. The results show that the deviation between the predicted value of the model and the actual value is less than 1.5%. The results show that the oil content decreases by 61% and the amount of anaerobic digestion gas production increases by 59% under the absorbed dose of 11.76 kGy, pH of 8.6, and the hydrogen peroxide concentration of 3.5 mmol/L, compared with those of the unirradiated wastewater. The gas chromatography and Fourier transform infrared spectroscopy analysis results show that there are more biodegradable organic substances in the wastewater after irradiation. Graphical abstract: Image 1 Highlights: We explored the best pre-treatment conditions for AD of kitchen wastewater. The predicted and actual experimental gas production values differed by 1.4%. Upon γ-ray pre-treatment, oil content of kitchen wastewater decreased by 61%. Gas production generated through AD increased by 59%. Enhancement of wastewater AD performance was related to changes in organic matter.